Building Digital Capacity: An Analysis of IT Training Programs and Their Impact: Membangun Kapasitas Digital: Analisis Program Pelatihan TI dan Dampaknya - Mochamad Slamet Abidin; Isna Fitria Agustina; Septi Wulandari; Oriza Satyva (International Consortium of Education and Culture Research Studies, 2025)
General Background Mastery of information technology constitutes an essential competency for contemporary workforce participation and vocational adaptability. Specific Background Vocational high schools hold the responsibility of equipping students with relevant technological proficiencies through structured training frameworks. Knowledge Gap Although project-based methodologies offer collaborative learning contexts, practical implementation reveals various operational challenges regarding mentorship structures, resource accessibility, and curriculum integration. Aims This case study evaluates the outcomes of project-based information technology training targeting student capabilities at SMK Negeri 1 Jabon. Results Findings indicate that the training significantly increases technical competence in software operation, network understanding, and graphic design, while simultaneously developing interpersonal soft skills and elevating academic motivation. Novelty This research specifically identifies holistic project-based learning as a vital mechanism for aligning vocational capabilities with digital era demands through structured industry collaboration. Implications Educational institutions must continuously integrate practical technology instruction into core curricula supported by intensive mentoring to produce adaptive vocational graduates. Highlights: Practical technology instruction significantly advances software operation, network understanding, and graphic design capabilities. Collaborative project activities successfully foster essential interpersonal communication and problem-solving attributes. Structured curriculum integration and intensive mentorship remain vital for sustaining student motivation. Keywords: Information Technology Training, Project Based Learning, Student Competencies, Vocational Education, Technical Skills